1992
DOI: 10.1084/jem.176.2.469
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the low affinity receptor for immunoglobulin E on mouse mast cells and macrophages as Fc gamma RII and Fc gamma RIII.

Abstract: In addition to their well characterized high affinity immunoglobulin E (IgE) receptors (Fc epsilon RI) mast cells have long been suspected to express undefined Fc receptors capable of binding IgE with low affinity. In this paper, we show that Fc gamma RII and Fc gamma RIII, but not Mac-2, on mouse mast cells and macrophages bind IgE-immune complexes. This binding is efficiently competed by 2.4G2, a monoclonal antibody against the extracellular homologous region of both Fc gamma RII and Fc gamma RIII. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 35 publications
7
77
0
Order By: Relevance
“…Stimulation of mast cells through Fc␥RIII with oligomeric IgE induced serotonin secretion in vitro (5). This study provided the first evidence that IgE could bind Fc␥RIII and stimulates mast cells via this receptor.…”
Section: Ige-mediated Activation Of Nk Cellsmentioning
confidence: 78%
See 1 more Smart Citation
“…Stimulation of mast cells through Fc␥RIII with oligomeric IgE induced serotonin secretion in vitro (5). This study provided the first evidence that IgE could bind Fc␥RIII and stimulates mast cells via this receptor.…”
Section: Ige-mediated Activation Of Nk Cellsmentioning
confidence: 78%
“…It was demonstrated that IgE binds to Fc␥RIII on a mast cell line in vitro and causes degranulation (5). Furthermore, when IgE-mediated anaphylaxis was compared between Fc␥RIII Ϫ/Ϫ and wildtype (wt) 3 mice, the anaphylaxis was more severe in wt mice than in Fc␥RIII Ϫ/Ϫ mice (6).…”
Section: Ige-mediated Activation Of Nk Cellsmentioning
confidence: 99%
“…Serum IgG levels are generally much higher than IgE levels. Consequently, although IgE IC can interact with mouse FcγRIIb and FcγRIII, at least in vitro at 4°C (30), the quantity of IgG IC is likely to be considerably higher than the quantity of IgE IC in the same animal. With this in mind, we hypothesized that IgG-but not IgE-mediated anaphylaxis might be accompanied by a change in FcγRIII expression by nucleated blood cells.…”
Section: Resultsmentioning
confidence: 99%
“…IgE ICs bound as efficiently as IgG2b ICs to mFcγRIV, less efficiently to mFcγRIIB and mFcγRIIIA, and not detectably to mFcγRI. mFcγRIIB and mFcγRIIIA were previously reported to behave as low-affinity IgE receptors (15). IgE ICs of the 2 allotypes bound comparably to mFcγRIV ( Figure 1C).…”
Section: Mfcγriv But Not Hfcγriii Is a Low-affinity Ige Receptormentioning
confidence: 97%